2021
DOI: 10.1093/plankt/fbab047
|View full text |Cite
|
Sign up to set email alerts
|

Krill diel vertical migration in Southern Patagonia

Abstract: Diel vertical migration (DVM) of krill was studied throughout 36 h at a fixed station (46.05°S, 66.19°W; 98-m depth) located in the center of the San Jorge Gulf, Southern Patagonia area, during February 2014. Using an echosounder system, combined with an autonomous Video Plankton Recorder (Auto-VPR) and Jacknet samplings, we describe the migration pattern, the associated biomass and the macrozooplankton species involved. The net sampling and the Auto-VPR images allowed us to identify the krill species detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…According to our data, DVM might explain the low density of E. lucens found in samples collected in previous studies in Golfo Nuevo 13 , 60 . It has been demonstrated that both juvenile and adult stages of E. lucens migrate extensively throughout the water column 82 and remained at or near the bottom during daylight hours and ascending toward the surface at night as shown for the Golfo San Jorge in Argentinean Patagonia 45 . Here, the highest abundance of E. lucens in older stages was found aggregated near the bottom.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to our data, DVM might explain the low density of E. lucens found in samples collected in previous studies in Golfo Nuevo 13 , 60 . It has been demonstrated that both juvenile and adult stages of E. lucens migrate extensively throughout the water column 82 and remained at or near the bottom during daylight hours and ascending toward the surface at night as shown for the Golfo San Jorge in Argentinean Patagonia 45 . Here, the highest abundance of E. lucens in older stages was found aggregated near the bottom.…”
Section: Discussionmentioning
confidence: 97%
“…This behavior involves a vertical migration to deeper waters before dawn and an upward migration at dusk towards the surface layer 41 , 42 . During DVM, zooplankton migrate to the surface to feed at night and then return to deeper depths to reduce predation risk from visual predators such as zooplanktivorous fish 43 45 . Studies have shown that larger zooplankton in advanced developmental stages, such as late juveniles and adults, tend to undergo DVM to greater depths compared to smaller individuals in earlier developmental stages 46 48 .…”
Section: Introductionmentioning
confidence: 99%
“…This coincides with the main depth range of Euphausia lucens (Gibbons et al ., 1991). Furthermore, D. gahi and Euphausiacea show the same diel vertical migration pattern (Nocera et al ., 2021). The SSC of D. gahi in 2020 fed on smaller amounts of Euphausiacea, due to lower abundances of Euphausiacea during winter (Sabatini & Colombo, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of krill distribution, horizontal displacements over time are poorly understood. A key driver of horizontal advection is obviously oceanographic currents (Bestley et al, 2018;McBride et al, 2021;Nocera et al, 2021). However, krill can also swim at high speeds for extended periods of time against local currents (Krafft et al, 2015).…”
Section: Spatiotemporal Predator-prey Linkagesmentioning
confidence: 99%